FTSE KLCI DYNAMICS: IMPACT OF REAL INTEREST RATES AND INDUSTRIAL PRODUCTION INDEX - Md Isa, Evawaynie Valquis; Islam, Md. Aminul; Amir, Aliana Shazma Amir (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study examines the impact of the Real Interest Rate (RIR) and the Industrial Production Index (IPI) on the movements of the FTSE Bursa Malaysia KLCI (FTSE KLCI) from 2008 to 2023. As Malaysia transitions toward a more market-based financial system, critical issues arise regarding how macroeconomic variables affect stock market behaviour in an emerging market context. Despite the growing body of literature, there remains a gap in understanding how monetary and real sector indicators jointly influence stock market dynamics, particularly in the Malaysian context. RIR, which reflects the real cost of capital, affects corporate borrowing and speculative investment, while IPI serves as a proxy for economic productivity and industrial growth. This study applies a Random Effects Model to 16 years of FTSE KLCI data, using key diagnostics (ADF, VIF, Breusch-Pagan, Durbin-Watson) to ensure robust, reliable results. Findings show that RIR exerts a significant negative effect on stock market movements, suggesting that higher real interest rates act as a stabilizing force. In contrast, IPI has a positive and significant relationship with stock movements, indicating that industrial expansion increases market responsiveness. These results support the semi-strong form of the Efficient Market Hypothesis (EMH), affirming that public macroeconomic information is swiftly absorbed into asset prices. With strong explanatory power (R² = 0.9925), the study offers key insights into how macroeconomic factors shape stock market dynamics in Malaysia’s growing capital market.